Answer:
1 +6 x + 12 x 2 + 8x 3
Explanation:
We must use our knowledge of the binomial expansion:
Method 1:
We can use:
(
x
+
1
)
n
=
1
+
n
x
+
n
(
n
−
1
)
2
!
x
2
+
n
(
n
−
1
)
(
n
−
2
)
3
!
x
3
+
...
Substituting
n
=
3
and
x
for
2
x
⇒
(
2
x
+
1
)
3
=
1
+
(
3
⋅
2
x
)
+
3
⋅
2
2
!
⋅
(
2
x
)
2
+
3
⋅
2
⋅
1
3
!
⋅
(
2
x
)
3
=
1
+
6
x
+
12
x
2
+
8
x
3
Method 2:
We can use:
(
A
+
B
)
n
=
A
n
+
(
n
1
)
A
n
−
1
B
1
+
(
n
2
)
A
n
−
2
B
2
+
...
Letting
A
=
2
x
and
B
=
1
for this circumstance:
(
2
x
+
1
)
3
=
(
2
x
)
3
+
(
3
1
)
(
2
x
)
2
(
1
)
+
(
3
2
)
(
2
x
)
1
(
1
)
2
+
(
3
3
)
(
2
x
)
0
(
1
)
3
=
8
x
3
+
12
x
2
+
6
x
+
1
Explanation: